PENINGKATAN KETERAMPILAN MENULIS MENGGUNAKAN METODE PBL KOLABORASI MIND MAPPING - Darmuki, Agus; Hidayati, Nur Alfin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the writing skills of PBSI FKIP UMK students in Semester 4 of the 2024/2025 Academic Year using the Mind Mapping Collaborative Problem Based Learning (PBL) method. The problem faced by students is the lack of effective and structured writing skills. The solution offered is to use the Mind Mapping Collaborative PBL method which can help students improve their writing skills. This study uses a classroom action research method with 30 PBSI FKIP UMK students in Semester 4 of the 2024/2025 Academic Year. The instruments used are writing tests, observations, and interviews. The results of the study indicate that the Mind Mapping Collaborative PBL method can significantly improve students' writing skills. Students can improve their ability to organize ideas, structure writing, and develop effective sentences. The conclusion of this study is that the Mind Mapping Collaborative PBL method can be an effective alternative to improve students' writing skills.